Effects of Joint Gymnastics Exercise Intervention on Improving Functional Ability of the Elderly - Caturini, Endang; Ariani, Dwi; Khadijah, Siti (Interest : Jurnal Ilmu Kesehatan, 2024)
Background: The elderly experience changes in the musculoskeletal system in the form of joint disorders that attack the joints and supporting tissue structures around the joints causing pain, loss of physical function, and disability. This requires management to reduce joint pain and improve muscle movement, function, strength, and endurance using joint gymnastics/rheumatism. The purpose of this study was to improve the ability of physical functioning in the elderly. Methods: Quasi-experimental research with pre-post test design. The number of samples was 42 elderly people. This study measured the ability of physical function in the elderly. The research instrument used the KOOS (Knee injury and Osteoarthritis Outcome Score) questionnaire. Data were analyzed using the Wilcoxon signed ranks test. Results: Research shows the majority of respondents are > 59 years old, and the majority are women (62.2%). There was an increase in knowledge with an increase in score of 2.19 and functional ability with an increase of 21.71 which was described in 4 sections, namely for pain score increased by 7.59, sign and symptom score increased by 7.09, ADL score increased by 2.76 and quality of life score increased by 4.26.  There was a significant effect (p = 0.000) of joint gymnastics training interventions on improving knowledge and functional abilities. Conclusion: There is an effect of joint gymnastics exercise interventions on improving knowledge and functional abilities.  Suggestion: the application of joint gymnastics exercises is needed as an additional intervention in the community and to improve functional ability in the elderly.